2018
DOI: 10.1111/emre.12163
|View full text |Cite
|
Sign up to set email alerts
|

Performance of the Firms in a Free‐Trade Zone: The Role of Institutional Factors and Resources

Abstract: Many countries have tried to establish free zones in order to strengthen the competitive advantage of their local companies in global competition. Judging the role of free zones in the performance of companies without analyzing the relevant institutional factors can be confusing, especially in countries like Iran where the government extensively intervenes in the economy. In such economies, institutional factors (institutional support, political relationship, and legitimacy) coupled with resources (financial, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 119 publications
(181 reference statements)
0
19
0
2
Order By: Relevance
“…According to Teifenbrun [ 6 ] and Akbari et al [ 7 ], an FTZ refers to an area where goods may be landed, handled, manufactured, or reconfigured, and then re-exported without the intervention of customs authorities. In the zones, multiple institutional incentives such as free movement of goods and people and preferential taxation are provided.…”
Section: Introductionmentioning
confidence: 99%
“…According to Teifenbrun [ 6 ] and Akbari et al [ 7 ], an FTZ refers to an area where goods may be landed, handled, manufactured, or reconfigured, and then re-exported without the intervention of customs authorities. In the zones, multiple institutional incentives such as free movement of goods and people and preferential taxation are provided.…”
Section: Introductionmentioning
confidence: 99%
“…Jenkins and Arce (2016) probed into the backward linkage and its regional economic driving effect of the export processing zones. Akbari et al (2018) surveyed 151 companies located in the Anzali Free Trade and showed its positive impact on the firms' competitive advantage and performance. Meng and Zeng (2019) summarized the success factors of the Shanghai free trade zone and other free economic zones.…”
Section: Literature Reviewmentioning
confidence: 99%
“…There are various approaches to the development of territorial entities in the form of special economic zones. One way is investment in free zones; that is, specific areas of a country in which trade tariffs are normal, rationing is eliminated, and bureaucracy that hinders attraction of new business and foreign capital is diminished (Akbari, Azbari, & Chaijani, 2018).…”
Section: Problem Statementmentioning
confidence: 99%